A Combined Approach to Safety and Security of IoT by Applying Fault Tree Analysis and Attack Trees with Minimal Cut Sets - Karim, Mohammad Rezaul; Kabir, Sohag; Lei, Ci; Lefticaru, Raluca; Abdul Baset, Mohammad (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2025)
The rapid proliferation of Internet of Things (IoT) systems introduces complex safety and security challenges, as traditional frameworks often treat these aspects separately, overlooking critical interdependencies. This study proposes a unified methodology integrating Fault Tree Analysis (FTA) and Attack Trees (AT) with Minimal Cut Sets (MCS) to holistically assess IoT safety and security. FTA systematically identifies root causes of system failures, while AT models attack vectors and their probabilities. By deriving MCS—minimal combinations of safety faults and security breaches—the approach reveals critical scenarios where failures and attacks interact, enabling prioritized mitigation. Applied to a real-world IoT dataset (BoTNeTIoT-L01), the framework identified key vulnerabilities, such as Data_Corruption (safety probability: 0.005) linked to Mirai attacks (security probability: 0.01), demonstrating how integrated MCS enhance risk visibility. Quantitative analysis (mean safety: 0.005, variance: 0.000006) confirmed the methodology’s effectiveness in capturing interdependencies across IoT layers (Perception, Network, Data Processing, Application). Results emphasize that combined safety-security analysis prevents isolated risk assessments, offering actionable insights for resilient IoT design. The study concludes that integrating FTA-AT-MCS bridges existing gaps in IoT dependability, enabling targeted resource allocation and adaptive strategies against evolving threats. This approach advances IoT ecosystems’ safety, security, and trustworthiness in interconnected environments.